Water disinfection by solar radiation in a green house effect device. (16th March 2010) - Valenzuela, E.; Alvarez, P.E.; Eapen, D.; Brito, D.; Camas, K.; Diaz, G.; Diaz, K.; Espinosa, F.; Vazquez, C.
The water-borne diseases are major concerns in developing countries since they are the main cause of sickness and death among the population in rural communities. The traditional methods such as chlorination and the use of fuelwood to boil water has important environmental consequences and in some cases are rejected by population. The solar water heaters are considered as an effective, low cost and sustainable solution for water disinfection in rural areas. In this work, a solar water heater of greenhouse effect was built and characterised. Water samples were collected from two contaminated water sources, treated in the solar device and then analysed to validate the complete elimination of pathogenic microorganisms.